2017
DOI: 10.2174/1574888x11666160614103404
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Cytokines in the Differentiation of Mesenchymal Stem Cells: A Review

Abstract: Mesenchymal stem cells (MSCs) are stromal origin cells with multilineage differentiation capacity. The immunoregulatory properties of MSCs can be interfered effectively by cytokines. Cytokines, produced by a broad range of cells, act at the systemic level to influence biological phenomena such as inflammation, wound healing, organogenesis and oncogenesis. Cytokines also play vital roles in the differentiation of MSCs into several cell lineages. This review summarizes on how cytokines can affect MSCs differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Abnormal immunoregulation by MSCs can lead to several autoimmune diseases [4]. Moreover, MSCs exert considerable therapeutic effects on several autoimmune diseases owing to their multilineage differentiation potential and highly immunoregulatory properties [23,24]. In our previous study, we found that impairment in the immunoregulatory functions of MSCs played a key role in the pathogenesis of AS [7].…”
Section: Mscs Are One Of the Most Important Immunoregulatory Cell Typmentioning
confidence: 94%
“…Abnormal immunoregulation by MSCs can lead to several autoimmune diseases [4]. Moreover, MSCs exert considerable therapeutic effects on several autoimmune diseases owing to their multilineage differentiation potential and highly immunoregulatory properties [23,24]. In our previous study, we found that impairment in the immunoregulatory functions of MSCs played a key role in the pathogenesis of AS [7].…”
Section: Mscs Are One Of the Most Important Immunoregulatory Cell Typmentioning
confidence: 94%
“…Cytokines are synthesized mainly by the immune and nervous system and are responsible for the regulation of differentiation, inflammation, immune responses, cell apoptosis, and necrosis via transmitting signals between cells (Totsch and Sorge, 2017 ; Zahari et al, 2017 ). Additionally, cytokines contribute significantly to pain arising from nociceptor activation.…”
Section: Mechanistic Insights Into the Dialog Between Neuron And Mast Cellmentioning
confidence: 99%
“…During the perinatal period, ESC-derived AECs can rescue fetal lung explants from pulmonary hypoplasia and vascular rupture in vitro [ 72 ]. It is necessary to screen MSC-related markers through the laboratory and then carry out verification experiments and quantitative determination of biological activity, to lay a foundation for the application and promotion of MSCs which can affect the proliferation and function of immune cells, including dendritic cells, NK cells, and T and B lymphocytes [ 43 , 73 , 74 ]. It should be noted that tumor formation has not yet been verified after MSC treatment in vivo [ 59 , 61 , 66 ], but it does not mean that MSCs have no potential for teratogenic and carcinogenic.…”
Section: Current Challenges In Msc Treatmentmentioning
confidence: 99%